PERAN HUKUM DALAM PEMBANGUNAN EKONOMI DI INDONESIA: ARAH KEBIJAKAN PEMERINTAH MENGHADAPI PRAKTEK DUMPING - Fahmi Fairuzzaman (Lex Renaissance, 2021)
This research raises issues, firstly, the direction of policies implemented by the Government of Indonesia to deal with dumping practices carried out by other countries against Indonesia. Secondly, the role of law in economic development in Indonesia related to preventing fraudulent dumping practices. The method used is normative legal research. The results of the study conclude that first, the policy directed by the Government of Indonesia in dealing with the fraudulent practice of dumping by other countries against Indonesia is carried out by ratifying the Agreement for the Establishment of the World Trade Organization (WTO). With this ratification, Indonesia must then adjust its policies in international trade to comply with WTO provisions, including implementing anti-dumping policies in accordance with the Anti-Dumping Agreement. Second, the law acts as a tool for carrying out economic development. The law acts as a tool to prevent dumping practices in order to support the implementation of economic development in Indonesia.Key Words: Dumping; law and economic developmentAbstrakPenelitian ini mengangkat permasalahan, pertama, arah kebijakan yang diberlakukan Pemerintah Indonesia untuk menghadapi praktek dumping yang dilakukan oleh negara lain terhadap Indonesia. Kedua, peran hukum dalam pembangunan ekonomi di Indonesia terkait dengan pencegahan praktek curang dumping. Metode yang digunakan adalah penelitian hukum normatif. Hasil penelitian menyimpulkan, pertama, arah kebijakan yang diberlakukan Pemerintah Indonesia dalam menghadapi praktek curang dumping oleh negara lain terhadap Indonesia dilakukan dengan meratifikasi Perjanjian Pembentukan Organisasi Perdagangan Dunia (WTO). Dengan ratifikasi tersebut Indonesia kemudian harus menyesuaikan kebijakannya dalam perdagangan internasional agar sesuai ketentuan WTO, termasuk menerapkan kebijakan anti-dumping sesuai dengan Anti-Dumping Agreement. Kedua, hukum berperan sebagai alat untuk melaksanakan pembangunan ekonomi. Hukum berperan sebagai alat untuk mencegah praktek dumping guna mendukung terlaksananya pembangunan ekonomi di Indonesia.Kata Kunci: Dumping; hukum dan pembangunan ekonomi